FUTURE PROFESSIONAL EDUCATION SPECIALISTS’ MASTERING OF PROJECT METHODOLOGY OF CREATING PEDAGOGICAL SITUATIONS IN THE SERVICE SECTOR - Savchenko, Larysa; Safian, Karyna; Kulinka, Yuliia; Kharadzhian, Natalia; Kopylova, Oksana (Revista Inclusiones, 2020)
The article reveals the problems of mastering by future specialists of the project methodology of creating pedagogical situations in higher education institutions as a means of improving the quality of education. Objectives of the article: to determine the influence of the project method on the creation of pedagogical situations in the process of teaching students; the choice of logic and mechanism of design actions depends on the purpose and the initial conceptual position regarding the subject reincarnates; to study the influence of pedagogical situations on the quality of education in the higher pedagogical school; to diagnose the implementation of the projects method and pedagogical situations in the process of education at the university. The project method provides the presence of a problem that requires integrated knowledge and research for its solution. The results of the planned activities should have practical, theoretical and cognitive significance. Modeling of pedagogical situations is the process of formation of situations-models which simulate the state and dynamics of the educational process and fix the contradiction between the achieved and desired in the personality development in a certain time interval. During the forming experiment, pedagogical situations were used to form the professional competence of the future specialist.